Polymeric Multivalent Fc Binding Peptides‐Fabricated Clinical Compounding Bispecific Antibody Potentiates Dual Immunotherapy Targeting PD1 and CTLA‐4 - Zongyu Liu; Hongyu Chu; Weidong Zhao; Chenguang Yang; Tongjun Liu; Na Shen; Zhaohui Tang (Advanced Science)
Abstract Dual Opdivo plus Yervoy immunotherapy, targeting the immune checkpoints PD1 and CTLA‐4, is successful in clinical use. However, it is associated with a high incidence of adverse events, and its therapeutic efficacy needs improving. In this study, polymeric multivalent Fc‐binding peptides (PLG‐Fc‐III‐4C) are employed to fabricate a bispecific antibody (PD1/CTLA‐4 BsAb) to potentiate dual immunotherapy targeting PD1 and CTLA‐4. The PD1/CTLA‐4 BsAb is prepared by mixing PLG‐Fc‐III‐4C with aPD1 and aCTLA‐4 in an aqueous solution for 3 h using the clinically optimal 3:1 proportion of aPD1 to aCTLA‐4. PD1/CTLA‐4 BsAb significantly inhibits tumors in MC38 colon cancer‐bearing mice more effectively than the combination of aPD1 and aCTLA‐4, with tumor suppression rates of 96.8% and 77.3%, respectively. It also induces a higher percentage of CD8+ T cells and increases the secretion of effector cytokines while reducing Treg levels in tumors compared to phosphate‐buffered saline, indicating significant tumor immunity regulation. Mechanistically, a 6.3‐fold increase in PD1/CTLA‐4 BsAb accumulation in tumors due to the tumor targeting ability of aPD1, and the PD1/CTLA‐4 BsAb significantly reduces the adverse colitis event in healthy mice, compared to aPD1 and aCTLA‐4. Thus, these findings provide a novel approach to enhance antitumor therapy using aPD1 and aCTLA‐4.